Combined hypoxemic and hypotensive insults altered physiological responses and neurofunction in a severity-dependent manner following penetrating ballistic-like brain injury in rats. Issue 4 (October 2015) - Leung, Lai Yee; Deng-Bryant, Ying; Shear, Deborah; Tortella, Frank
Abstract : BACKGROUND: Traumatic brain injury often occurs with concomitant hypoxemia (HX) and hemorrhagic shock (HS), leading to poor outcomes. This study characterized the acute physiology and subacute behavioral consequences of these additional insults in a model of penetrating ballistic-like brain injury (PBBI). METHODS: Rats were randomly assigned into sham control, HX + HS (HH), 5% PBBI alone, 5% PBBI + HH, 10% PBBI alone, and 10% PBBI + HH groups. Mean arterial pressure, heart rate, and breathing rate were monitored continuously. In the combined injury groups, animals were subjected to 30-minute HX (Pao2, 30–40 mm Hg) and then 30-min HS (mean arterial pressure, 40 mm Hg) followed by fluid resuscitation with lactated Ringer's solution after PBBI or sham PBBI. Motor function was assessed using the rotarod task at 7 days and 14 days after injury. Cognitive function was assessed in the Morris water maze task from 13 days to 17 days after injury. RESULTS: Combined HH caused acute bradycardia that was reversed by fluid resuscitation. During HX phase, tachypnea was observed in all HH groups. Persistent bradypnea was detected in 10% PBBI + HH group during the resuscitation phase. PBBI produced significant decrements in motor performance (vs. sham and HH groups). Additional insults significantly worsened motor deficits following 5% PBBI but not 10% PBBI. Both 5% PBBI and 10% PBBI produced significant cognitive deficits in the Morris water maze task with worsened deficits evident following the more severe injury (i.e., 10% PBBI). Alternatively, rats subjected to 5% PBBI + HH exhibited cognitive impairment that was significantly worse compared with 5% PBBI alone, whereas this worsening effect was not detected in the 10% PBBI groups. CONCLUSION: This study characterized the physiological responses and neurobehavioral profiles following combined PBBI and HH. Ten percent PBBI produces motor and cognitive deficits, which may exceed a sensitivity threshold capacity. In contrast, 5% PBBI produces a lower, albeit significant, magnitude of deficits and thus provides a more sensitive screen for evaluating the cumulative effects of additional insults, which were indeed demonstrated to significantly worsen outcome.